Resistance patterns and transmission of mono- and polyresistant TB: clinical impact of WGS - Dohál, Matúš; Dvořáková, Věra; Šperková, Miluše; Pinková, Martina; Spitaleri, Andrea; Rasmussen, Erik Michael; Škereňová, Mária; Krivošová, Michaela; Gondáš, Eduard; Porvazník, Igor; Solovič, Ivan; Cirillo, Daniela Maria; et al. (JAC-antimicrobial resistance, 2023)
Abstract Objectives Rapidly diagnosing drug-resistant TB is crucial for improving treatment and transmission control. WGS is becoming increasingly accessible and has added value to the diagnosis and treatment of TB. The aim of the study was to perform WGS to determine the rate of false-positive results of phenotypic drug susceptibility testing (pDST) and characterize the molecular mechanisms of resistance and transmission of mono- and polyresistant Mycobacterium (M.) tuberculosis. Methods WGS was performed on 53 monoresistant and 25 polyresistant M. tuberculosis isolates characterized by pDST. Sequencing data were bioinformatically processed to infer mutations encoding resistance and determine the origin of resistance and phylogenetic relationship between isolates studied. Results The data showed the variable sensitivity and specificity of WGS in comparison with pDST as the gold standard: isoniazid 92.7% and 92.3%; streptomycin 41.9% and 100.0%; pyrazinamide 15% and 94.8%; and ethambutol 75.0% and 98.6%, respectively. We found novel mutations encoding resistance to streptomycin (in gidB) and pyrazinamide (in kefB). Most isolates belonged to lineage 4 (80.1%) and the overall clustering rate was 11.5%. We observed lineage-specific gene variations encoding resistance to streptomycin and pyrazinamide. Conclusions This study highlights the clinical potential of WGS in ruling out false-positive drug resistance following phenotypic or genetic drug testing, and recommend this technology together with the WHO catalogue in designing an optimal individualized treatment regimen and preventing the development of MDR TB. Our results suggest that resistance is primarily developed through spontaneous mutations or selective pressure.